Effect of rhizophere temperature on tomato root volume production - Ho, Angelina Mei Yi; Ahmad, Desa; Mohammud, C. H. (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
The effect of root zone cooling on tomato root density was investigated under a greenhouse structure at Malaysian Agricultural Research and Development Institute (MARDI). Heat tolerance tomato variety was grown in a tropical greenhouse with pre-installed buried cooling pipes to chill the root zone. The experiment was conducted in a Completely Randomized Design with 4 temperature treatments, 15, 20, 25 and the control (with no cooling pipes installed, approximately 30). Each treatment had 3 replicates. The results reveal that root zone cooling significantly increased the root volume production. The study also shows that most of the roots were concentrated within the top layer about 10cm below the surface of the planting media comprising of cocopeat, burnt rice husk and perlite in a ratio of 7:3:2 respectively. The best chilled media temperature for highest root volume production was at 25.